If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + -4 = 2 Reorder the terms: -4 + 2z = 2 Solving -4 + 2z = 2 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 2z = 2 + 4 Combine like terms: -4 + 4 = 0 0 + 2z = 2 + 4 2z = 2 + 4 Combine like terms: 2 + 4 = 6 2z = 6 Divide each side by '2'. z = 3 Simplifying z = 3
| 4x+8y=30 | | -2(3x+8)=20 | | 100+.15x=150+.10x | | 100+.15x=150+.10c | | -x+25=3x+1 | | 400-4x+3x^2=0 | | -8x+10(5)=40 | | 3x+12+2x+2x=47 | | 18x+3y= | | 4x+1=-6 | | -3+4t+-7=9 | | -2c+4=-6c | | x+24=4x+6 | | 9+2(9+4j)= | | 4x-6(-2)=-72 | | h=8(5) | | 4x+11=121x | | 23x+5=120x | | 10y+10y+10x= | | 5.3(x+5)=x+21 | | 4x+25=x+4 | | 2xy-2n=14 | | 2(-4)+7-4(-4)=15 | | -5(-5)+y=30 | | -7x-40=-12x+45 | | x+16=3x+6 | | -2=7x-6x-6 | | 10x+6=104x | | -31-11x=35-8x | | 3(2)-y=9 | | 6b-6b+32=16 | | 2b+3c=12 |